Project Delay Analysis Using Fault Tree Analysis (FTA) Method And Failure Mode And Effect Analysis (FMEA) Method (Case Study of the Karian Rangkasbitung Dam Development Project) - Maddeppungeng, Andi; Asyiah, Siti; Ujianto, Rifky; Akbar, Bagus Istigosah; Setiawati, Dwi Novi (Jurnal Fondasi, 2023)
The Karian Dam Project is one of a total of 48 dam construction strategic projects in Indonesia that have experienced delays. Based on Addendum 6, the Karian Dam Project is targeted for completion in March 2021. However, the Karian Dam Project experienced delays in several works. This study discusses the factors of delay, the location of the risk of delay, and the work item assistance that causes delays in the Karian Dam Project. The research method used in this study is a quantitativ. Data collection was carried out using questionnaires and interviews. The obtained data is then analyzed using the Fault Tree Analysis (FTA) method to find the source of risk that is the cause of the delay. The subsequent analysis uses the Failure Mode and Effect Analysis (FMEA) method to assess the risks that have been identified using the FTA method for risk capture. According to the findings, there are 47 potential sources of delay in the FTA method. After calculating the probability index, it is found that activity A9-1 (planning and implementation) has the highest probability index value of 4. The FMEA method obtains the highest value of the highest Risk Priority Number (RPN) there is R-42 (planning change) with an RPN value of 64, and on arrest risk using the search risk matrix, as many as 9 risks are at high risk (high risk).